Early Rehospitalization After Kidney Transplantation: Assessing Preventability and Prognosis. Issue 12 (28th October 2013) - Harhay, M.; Lin, E.; Pai, A.; Harhay, M. O.; Huverserian, A.; Mussell, A.; Abt, P.; Levine, M.; Bloom, R.; Shea, J. A.; Troxel, A. B.; Reese, P. P.
Abstract Early rehospitalization after kidney transplantation (KT) is common and may predict future adverse outcomes. Previous studies using claims data have been limited in identifying preventable rehospitalizations. We assembled a cohort of 753 adults at our institution undergoing KT from January 1, 2003 to December 31, 2007. Two physicians independently reviewed medical records of 237 patients (32%) with early rehospitalization and identified (1) primary reason for and (2) preventability of rehospitalization. Mortality and graft failure were ascertained through linkage to the Scientific Registry of Transplant Recipients. Leading reasons for rehospitalization included surgical complications (15%), rejection (14%), volume shifts (11%) and systemic and surgical wound infections (11% and 2.5%). Reviewer agreement on primary reason (85% of cases) was strong (kappa = 0.78). Only 19 rehospitalizations (8%) met preventability criteria. Using logistic regression, weekend discharge (odds ratio [OR] 1.59, p = 0.01), waitlist time (OR 1.10, p = 0.04) and longer initial length of stay (OR 1.42, p = 0.03) were associated with early rehospitalization. Using Cox regression, early rehospitalization was associated with mortality (hazard ratio [HR] 1.55; p = 0.03) but not graft loss (HR 1.33; p = 0.09). Early rehospitalization has diverse causes and presents challenges as a quality metric after KT. These results should be validated prospectively at multiple centers to identify vulnerable patients and modifiable processes‐of‐care.